The relationship between parental emotional warmth and school bullying: The chain mediation role of social support and emotional regulation - Zhengwei Wan; Shuyu Huang (PLoS ONE, 2025)
This study explores the complex interplay between parental emotional warmth, social support, emotional regulation, and school bullying among students. Using a chain mediation model, we investigate how parental emotional warmth indirectly influences school bullying through the mediating roles of social support and emotional regulation. A sample of 566 students aged 10–13 participated in this study. The results indicate that parental emotional warmth significantly enhances social support, which in turn positively influences emotional regulation, thereby reducing school bullying behaviors. However, the direct effect of parental emotional warmth on school bullying was not significant. These findings highlight the importance of social support and emotional regulation as mechanisms through which parental emotional warmth affects school bullying. The study contributes to the theoretical understanding of the impact of family dynamics on children’s behavior and provides practical insights for developing multi-faceted interventions to prevent and reduce school bullying. Future research should employ longitudinal designs and diverse populations to further validate these findings and explore cultural variations.